Two-dimensional liquid chromatography and ion mobility-mass spectrometry for the multicomponent characterization of different parts of the medicinal plant Gynostemma longipes - Zheng, Wei; Li, Gang; Yang, Guang; Lu, Pengxin; Li, Qi; Zhang, Mengmeng; Yuan, Ming; Chen, Xiaojuan; Wang, Chenchen; Guo, Baolin; Ma, Baiping (Frontiers in Chemistry, 2023)
Herba Gynostemma (Jiaogulan) is an herbaceous plant of the genus Gynostemma in the family Cucurbitaceae. Gynostemma longipes has lipid-lowering activity, thus, it is used as a medicinal material. However, its medicinal using parts have been recorded as whole plants or aerial parts in different provincial quality standards; therefore, it is necessary to conduct a comprehensive compositional analysis of the different parts of G. longipes (rhizomes, stems, and leaves) used in traditional medicine. In this study, offline two-dimensional liquid chromatography-ion mobility-quadrupole time-of-flight mass spectrometry (2D-LC/IM-QTOF-MS) was used to analyze the different parts of G. longipes obtained from Shaanxi province, China. By combining the retention times, mass fragments, collision cross-section values, reference standards, and information concerning literature compounds, 396 components were identified from the three parts of the plant, including 94 groups of isomers, and 217 components were identified or tentatively identified as new compounds. In the rhizomes, leaves, and stems, 240, 220, and 168 compounds, respectively, were identified. Differential analysis of the compounds in the rhizomes and aerial parts was also carried out, and 36 differential components were identified, of which 32 had higher contents in the rhizomes. Therefore, these findings indicate that the number of chemical components and the content of major differential components are higher in the rhizomes than the leaves and stems of G. longipes from the Maobaling Planting Base in Pingli county, Shaanxi province. Thus, the rhizomes of G. longipes are also an important part for medicinal use. These results will contribute to the establishment of quality control methods for G. longipes.